Cardiac autonomic neuropathy in diabetes mellitus - Behera, Bijaya K.; K., Vishnu (International Journal of Research in Medical Sciences, 2017)
Background: The present study was conducted with an objective to study the prevalence of cardiac autonomic neuropathy (CAN) in patients with diabetes mellitus (DM) and its relation to duration, severity of DM, patient's age and BMI. Methods: This hospital based prospective study was conducted from August 2015 to September 2017, at M.K.C.G. Medical College Hospital, Berhampur, Odisha, India. Cross sectional study was design. A total number of 100 diagnosed patients of diabetes mellitus who were admitted in hospital or attended on OPD basis were taken for the study. Detailed history, clinical evaluation, laboratory investigations were carried out. The diagnosis of CAN was made by autonomic function tests. The CAN score of each patient was analysed. Database were generated based on age, duration of diabetes, severity of DM and BMI. Results: Out of 100 diabetic patients, 40 patients (23 males and 17 females) were selected for final analysis after excluding conditions causing cardiac autonomic neuropathy other than diabetes mellitus. All the patients were in the age group 21 to 70years. In the present study it was found that 57.5% of patients with DM had CAN and its incidence increased with severity of hyperglycemia, duration of DM, BMI and age of the patient. Conclusions: Cardiac autonomic neuropathy is a common and early complication of DM. Proper history taking to identify the symptoms related to CAN and performing simple autonomic tests in all patients of DM can identify cardiac autonomic neuropathy.